1997
DOI: 10.1016/s0168-9002(96)00981-3
|View full text |Cite
|
Sign up to set email alerts
|

Laterally resolved measurements of polycrystalline cesium iodide surfaces

Abstract: Laterally resolved measurements of polycrystalline cesium iodide surfaces Rudolf, Petra; Marchal, F.; Sporken, R.; Caudano, R.; dellOrto, T.; Almeida, J.; Braem, A.; Piuz, F.; Sgobba, S.; Paic, G. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, it has been observed that the thermal evaporation is the best choice forming a stoichiometric Cs:I ratio [21] as well as the highest absolute quantum efficiency (QE) compared to other preparation techniques [17][18][19][20]. Even with its enormous applications in a variety of fields discussed above, very few of the earlier studies in this field deal with characterization of CsI film structure [22][23][24][25][26][27]. X-ray diffraction (XRD) and transmission electron microscopy (TEM) are the two important techniques which are commonly used for the structural characterization.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that the thermal evaporation is the best choice forming a stoichiometric Cs:I ratio [21] as well as the highest absolute quantum efficiency (QE) compared to other preparation techniques [17][18][19][20]. Even with its enormous applications in a variety of fields discussed above, very few of the earlier studies in this field deal with characterization of CsI film structure [22][23][24][25][26][27]. X-ray diffraction (XRD) and transmission electron microscopy (TEM) are the two important techniques which are commonly used for the structural characterization.…”
Section: Introductionmentioning
confidence: 99%